A post structural analysis of the Binirayan Festival of Antique. - Moscoso, Chad Martin (No date of found.)
A Post Structuralist Analysis of the Binirayan Festival is written to relocate the study and analysis of the Binirayan into the literary perspective. It makes use mostly of Barthes's theories of the text and the interdisciplinary. This involves discussing some of the elements of the festival and bringing out and analyzing the texts found within. The study involved several trips to Antique, the gathering of Binirayan related literature and material, as well as a bit of internet research. Remarkably, numerous texts and intertexts can be found within the festival and its components which amde it possible to relocate the festival into literary studies. More about the text and the Binirayan will be discussed further in this thesis.
Thesis (Undergraduate, Bachelor of Arts in Literature)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Binirayan Festival -- Antique